2008
DOI: 10.1002/er.1406
|View full text |Cite
|
Sign up to set email alerts
|

An examination of exergy destruction in organic Rankine cycles

Abstract: SUMMARYThe exergy topological method is used to present a quantitative estimation of the exergy destroyed in an organic Rankine cycle (ORC) operating on R113. A detailed roadmap of exergy flow is presented using an exergy wheel, and this visual representation clearly depicts the exergy accounting associated with each thermodynamic process. The analysis indicates that the evaporator accounts for maximum exergy destroyed in the ORC and the process responsible for this is the heat transfer across a finite tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 46 publications
(44 reference statements)
2
56
0
Order By: Relevance
“…The losses in ORC are higher compared to the ETC. This is due to the evaporator, which is the main contributor in exergy losses in the ORC due its irreversibility associated with heat transfer [25]. In addition, existence of multiple components in the ORC system also adds up to the total losses in exergy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The losses in ORC are higher compared to the ETC. This is due to the evaporator, which is the main contributor in exergy losses in the ORC due its irreversibility associated with heat transfer [25]. In addition, existence of multiple components in the ORC system also adds up to the total losses in exergy.…”
Section: Resultsmentioning
confidence: 99%
“…Other study has recorded higher exergy efficiency for ORC using different organic fluid [17]. The exergy efficiency can be increased up to 36% by using modified ORC to include turbine bleeding or regenerative ORC [15,25]. Since ORC has higher available exergy, it is possible to use larger capacity electric generator.…”
Section: Resultsmentioning
confidence: 99%
“…Hung et al [13] discussed the irreversible loss of the key parts in ORC and found that the maximum irreversible loss happens in the evaporator. Analogously, Wei et al [14] showed that the greatest irreversible loss occurs in the evaporator when waste heat temperature varies from 610 K to 650 K. Usually, the greatest exergy loss is in the evaporator under the given conditions [15][16][17][18] and the smallest exergy loss is in the pump in ORC. But the magnitude of exergy loss conditions [15][16][17][18] and the smallest exergy loss is in the pump in ORC.…”
Section: Introductionmentioning
confidence: 95%
“…Also, many investigations on ORC are mainly focused on the choices of the working fluid [7][8][9][10][11][12] and its performance [13][14][15][16][17][18][19][20][21]. Hung et al [13] discussed the irreversible loss of the key parts in ORC and found that the maximum irreversible loss happens in the evaporator.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they investigated the effect of mass flow rate on the system performance and found out that as the mass flow rate increased the turbine inlet pressure and turbine rotational speed increased while the regenerator efficiency decreased. Mago et al [21] examined exergy destruction in basic and R-ORCs using the network topological methodology. It was found that the evaporator contributed the most to the exergy loss of both cycles, but the loss of exergy was reduced in the regenerative cycle.…”
Section: Introductionmentioning
confidence: 99%